Mycoparasitic activity of nine isolates of different strains of Trichoderma sp. on Rhizoctonia solani in Cowpea beans (Vigna unguiculata L.) - Garrido Flores, Cynthia (2021)
Rhizoctonia solani, a phytopathogen that causes “damping off”, affects all plants that are propagated by botanical seed in the germination and seedling phases. The objective was to evaluate the mycoparasitic activity of nine isolates of different Trichoderma strains on Rhizoctonia solani, using Cowpea beans (Vigna unguiculata L). The isolates were 'T20, T17, T9, T10, TSV2, TSV, T10’ from Trichoderma asperellum; T5 from Trichoderma viride and T327 from Trichoderma harzianum. A treatment only with Rhizoctonia solani was considered, as a virulence control and a treatment only with Cowpea beans as a control of the viability of the seed. The treatments were arranged in a complete randomized design with 10 repetitions. The dual confrontation technique was used in a potato-dextrose-agar (PDA) culture medium in a Petri dish, considering the experimental unit. Samples were taken from the colonization zone and observed under a microscope to verify parasitism. Percentage of germination, seedling emergence and incidence of fungus lick were evaluated. Trichoderma harzianum (T327) and Trichoderma asperelum (T17) presented higher germination and emergence of cowpea bean seedlings and the lowest percentages of incidence of fungus sucking (3.25 and 5.29 respectively), having mycoparasitic activity on Rhizoctonia solani, becoming an important biological alternative for its control.